2007
DOI: 10.1021/jm061006n
|View full text |Cite
|
Sign up to set email alerts
|

3-[(5-Chloro-2-hydroxyphenyl)methyl]-5-[4-(trifluoromethyl)phenyl ]-1,3,4-oxadiazol-2(3H)-one, BMS-191011:  Opener of Large-Conductance Ca2+-Activated Potassium (Maxi-K) Channels, Identification, Solubility, and SAR

Abstract: Compound 8a (BMS-191011), an opener of the cloned large-conductance, Ca2+-activated potassium (maxi-K) channel, demonstrated efficacy in in vivo stroke models, which led to its nomination as a candidate for clinical evaluation. Its maxi-K channel opening properties were consistent with its structural topology, being derived by combining elements from other known maxi-K openers. However, 8a suffered from poor aqueous solubility, which complicated elucidation of SAR during in vitro evaluation. The activity of 8a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 27 publications
(70 reference statements)
0
74
0
2
Order By: Relevance
“…5). Mass spectra for all PDMS-derivatized alcohols (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) are provided in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…5). Mass spectra for all PDMS-derivatized alcohols (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) are provided in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we assessed the effects of BMS-191011, which is a newly developed BK Ca channel opener 16,17) and the prototype BK Ca channel opener NS 1619 18) on the rat retinal circulation. We found that both BMS-191011 and NS 1619 caused the vasodilator responses of retinal arterioles in vivo; however, the responses to BMS-191011, but not to NS 1619, were diminished by intravitreal injection of iberiotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] However, the role of BK Ca channels in regulation of the retinal circulation remains unclear. The purpose of the present study, therefore, was to examine effects of two BK Ca channel openers, BMS-191011 16,17) and NS 1619, 18) on the rat retinal arterioles in vivo.…”
mentioning
confidence: 99%
“…1,2,4-Триазол-3-оны представляют интерес, главным образом, как фармакологически значи-мые соединения, активность которых зависит от характера заместителей у атомов N-2, N-4 и C-5 [1][2][3][4]. Среди них обнаружены вещества с противоопухолевыми свойствами [1], агонисты PPAR рецепторов [2] и антагонисты нейрокинина 1 (NK 1 ) [3].…”
Section: Introductionunclassified
“…Среди них обнаружены вещества с противоопухолевыми свойствами [1], агонисты PPAR рецепторов [2] и антагонисты нейрокинина 1 (NK 1 ) [3]. 2,5-Биарил-1,2,4-триазол-3-оны и 4,5-биарил-1,2,4-триазол-3-оны известны как активаторы калиевых (Maxi-K2) каналов [4]. Триазолоны могут найти применение и в аналитических целях -в качестве хемосенсоров ка-тионов Hg 2+ и Cu 2+ [5].…”
Section: Introductionunclassified